KARAKTERISTIK KITAB TAFSIR QOERAN DJAWEN - Zainab, Zainab (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2020)
AbstractQoeran Dajawen is a Qur’anic exegetical work in the Nusantara Archipelago, written as a solution in response to a religious condition in Indonesia, particularly in Surakarta city in the early 20thcentury. To uncover this exegetical work comprehensively, I use a descriptive-hermeneutical analysis. I argue that in interpreting the Qur’an, it employs an analytical method of interpretation (tahlili), highly articulated through the Sufi style approach. This can be seen that the author uses the concept of maqāmāt in interpreting many verses of the Qur’an. Furthermore, its source of interpretations highly relies on modernist Muslim literature, as it is closely associated with Muhammadiyah, the modernist Muslim organization in Indonesia.The uniqueness is that it is written in the Javanese-literary script (cacarakan) with Javanese krama inggil. The purpose is to facilitate the transmission of knowledge for the grassroots so that it is expected that they can adequately understand Islamic teachings. AbstrakKitab Tafsir Qoeran Djawen adalah sebuah karya tafsir Nusantara yang ditulis guna sebagai solusi atas runyamnya kondisi keagamaan di Indonesia khususnya Surakarta pada awal abad 20 M. Guna mengungkap kitab ini secara komprehensif, penulis menggunakan analisis deskriptif-hermeneutis. Sehingga dapat disimpulkan bahwa kitab ini menggunakan metode tahlili dalam aplikasi penafsirannya. Coraknya sendiri sangat kental dengan corak sufi. Hal ini ditandai dengan ditemukan banyaknya penafsiran-penafsiran yang menggunakan konsep maqāmāt. Sedangkan sumber-sumber yang dipakai tafsir ini cenderung menggunakan literatur-literatur berbau modernis, sebab tafsir ini lekat dengan organisasi Muhammadiyah. Keunikan yang menjadikan karakter tersendiri bagi kitab ini adalah penulisan tafsir yang menggunakan aksara cacarakan disertai bahasa Jawa krama inggil. Hal ini dilakukan guna mempermudah dalam transfer of knowledge (transfer pengetahuan) untuk memahami ajaran agama Islam secara komprehensif bagi kalangan akar rumput. Kata Kunci: Tafsir Qoeran Djawen, Karakteristik, Metode.